An Epitaxial Ferroelectric Tunnel Junction on Silicon. (8th September 2014) - Li, Zhipeng; Guo, Xiao; Lu, Hui‐Bin; Zhang, Zaoli; Song, Dongsheng; Cheng, Shaobo; Bosman, Michel; Zhu, Jing; Dong, Zhili; Zhu, Weiguang
<x xml:space="preserve">Abstract</x> Epitaxially grown functional perovskites on silicon (001) and the ferroelectricity of a 3.2 nm thick BaTiO3 barrier layer are demonstrated. The polarization‐switching‐induced change in tunneling resistance is measured to be two orders of magnitude. The obtained results suggest the possibility of integrating ferroelectric tunnel junctions as binary data storage media in non‐volatile memory cells on a silicon platform. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>